2021
DOI: 10.1128/jvi.01587-20
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Shared Neutralization Mechanism of Three Classes of Human Papillomavirus Type 58 Antibodies with Disparate Modes of Binding

Abstract: Human papillomavirus type 58 (HPV58) is associated with cervical cancer and poses a significant health burden worldwide. Although the commercial 9-valent HPV vaccine covers HPV58, the structural and molecular-level neutralization sites of the HPV58 complete virion are not fully understood. Here, we report the high-resolution (∼3.5 Å) structure of the complete HPV58 pseudovirus (PsV58) using cryo-electron microscopy (cryo-EM). Three representative neutralizing monoclonal antibodies (nAbs 5G9, 2H3 and A4B4) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…This is consistent with the Kaidar–Person study, which found that HPV58 has a 1.8-fold higher association with invasive cervical cancer than HPV52 ( 15 ). We can consider HPV type 58 an important pathogen, especially in Asia ( 16 ). Therefore, in patients who are positive for HPV type 58, especially those with persistent infection despite normal TCT results, attention needs to be paid and the indications for colposcopy may be relaxed as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the Kaidar–Person study, which found that HPV58 has a 1.8-fold higher association with invasive cervical cancer than HPV52 ( 15 ). We can consider HPV type 58 an important pathogen, especially in Asia ( 16 ). Therefore, in patients who are positive for HPV type 58, especially those with persistent infection despite normal TCT results, attention needs to be paid and the indications for colposcopy may be relaxed as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, reconstructions of papillomaviruses with full icosahedral symmetry imposed have produced maps limited to modest resolution; however, recently subparticle reconstruction approaches have been successfully used to obtain high resolution [ 16 , 17 , 36 ]. Consistent with this finding, we found that for the native papillomavirus the icosahedrally enforced reconstruction did not advance beyond 4.4 Å resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The complete T = 7d icosahedral papillomavirus capsid has previously been visualized to modest resolution by cryogenic electron microscopy (cryo EM) with icosahedral symmetry imposed during the reconstruction [ 4 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. No structural studies of papillomavirus capsids with 60-fold icosahedral symmetry imposed have exceeded 4.1–4.4 Å resolution [ 13 , 14 , 15 , 16 ]. The structure of HPV16 QV published by Guan et al at 4.3 Å showed there is likely inherent flexibility of the papillomavirus capsid as evidenced by the variability in capsid resolution, and differing capsid diameters [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The viral supernatants were collected by centrifugation for purification by calcium chloride gradient centrifugation ( 28 ). The 50% tissue culture infective dose (TCID50) was calculated to determine adenovirus titers according to the classical Reed-Muench method ( 29 ).…”
Section: Methodsmentioning
confidence: 99%